Advances in In Situ SiC Growth Analysis Using Cone Beam Computed Tomography - Salamon, Michael; Arzig, Matthias; Uhlmann, Norman; Wellmann, Peter (Materials Science Forum, 2019)
Computed Tomography is becoming a valuable method for the in-situ monitoring of vapor grown silicon carbide single crystals [1]. Already the two-dimensional X-ray radiography has shown the potential of surveilling the growth process [2] and its characteristic features like the evolution of the facet, the crystal volume or the source material structure from one imaging plane. Even though the demands on imaging capability of the applied X-ray components used for a tomographic analysis are higher than for two-dimensional imaging, the extension of this method to the third dimension is highly beneficial. It allows investigating the full geometry and three-dimensional location of the features and by this provides a more accurate analysis. In this contribution we present the physical characteristics and the latest advances of our technique for the visualization of facets.
Keywords: 3D In Situ Analysis; Computed Tomography; PVT Growth Process Surveillance

Analysis of the Morphology of the Growth Interface as a Function of the Gas Phase Composition during the PVT Growth of Silicon Carbide - Arzig, Matthias; Künecke, Ulrike; Salamon, Michael; Uhlmann, Norman; Wellmann, Peter (Materials Science Forum, 2022)
The growth conditions of 75 mm SiC crystals in the PVT process is varied by different methods while the temperature field is kept constant. The addition of graphite into the source material leads to the formation of an ordered step flow with step heights of 0.014 µm, while the addition of graphite into the source together with N2 doping changes the step kinetics on the main facet, leading to very large, bunched steps of 0.17 µm. When elemental Si was added into the source material large macro steps are formed on the whole crystal surface. While the doping induced step bunching is related to the incorporation kinetics, the large steps induced in Si-rich conditions are attributed the reduction of surface energy. With the variation of the inert gas pressure the morphology of the surface is altered, similarly. Under low pressure conditions (0.2 mbar) a fine step structure evolves, while at a high pressure (40mbar) large surface steps are formed on the whole growth interface. Large surface steps are strongly impeded in their lateral motion at defects permeating the growth interface. At these sites the formation of foreign polytypes is facilitated.
Created from Fastlane, Scopus look-up
Keywords: 4H-SiC; bulk growth; gas phase composition; polytype switch; PVT; step bunching

Comparison of achievable contrast features in computed tomography observing the growth of a 4H-SiC bulk crystal - Salamon, Michael; Arzig, Matthias; Wellmann, Peter; Uhlmann, Norman (Materials, 2019)
Today the physical vapor transport process is regularly applied for the growth of bulk SiC crystals. Due to the required high temperature of up to 2400 °C, and low gas pressure of several Mbar inside the crucible, the systems are encapsulated by several layers for heating, cooling and isolation inhibiting the operator from observing the growth. Also, the crucible itself is fully encapsulated to avoid impurities from being inserted into the crystal or disturbing the temperature field distribution. Thus, once the crucible has been set up with SiC powder and the seed crystal, the visible access to the progress of growth is limited. In the past, X-ray radiography has allowed this limitation to be overcome by placing the crucible in between an X-ray source and a radiographic film. Recently these two-dimensional attenuation signals have been extended to three-dimensional density distribution by the technique of computed tomography (CT). Beside the classic X-ray attenuation signal dominated by photoelectric effect, Compton effect and Rayleigh scattering, X-ray diffraction resulting in the crystalline structure of the 4H-SiC superimposes the reconstructed result. In this contribution, the achievable material contrast related to the level of X-ray energy and the absorption effects is analyzed using different CT systems with energies from 125 kV to 9 MeV. Furthermore the X-ray diffraction influence is shown by the comparison between the advanced helical-CT method and the classical 3D-CT.
CRIS-Team Scopus Importer:2019-12-10
Keywords: 3D in situ analysis; Bragg diffraction; Computed tomography; Helical-CT; PVT growth process surveillance

Growing bulk-like 3C-SiC from seeding material produced by CVD - Schuh, Philipp; Arzig, Matthias; Litrico, G.; La Via, F.; Mauceri, M.; Wellmann, Peter (physica status solidi (a), 2017)
We present a process to transfer CVD grown heteroepitaxial 3C-SiC on Si onto polycrystalline SiC, involving an etching step to get rid of the Si and a homogeneous carbon glue deposit, facilitating the resulting compound to be used as a seeding material for further growth process. In a sublimation sandwich setup, realized within an inductively heated physical vapor transport reactor, used for bulk growth of SiC, the thickness of the 3C-SiC seed was increased up to 850μm while keeping the cubic polytype. With the introduction of Ta as a carbon getter, the gas phase composition is optimized in order to achieve an improved growth front. Single crystalline growth is confirmed by Laue diffraction and Raman measurements. The Raman peaks are shifted to higher wavenumbers, indicating compressive stress in the grown samples. Furthermore, a scale up of the process is demonstrated, showing the feasibility of growing 3C-SiC on an area of 10.5cm in a 2inch setup featuring a thickness of approximately 570μ
Keywords: 3C-SiC; bulk crystals; layer transfer; physical vapor transport

Growth conditions and in situ computed tomography analysis of facetted bulk growth of SiC boules - Arzig, Matthias; Salamon, Michael; Uhlmann, Norman; Johansen, Bertil Andre; Wellmann, Peter (Materials Science Forum, 2018)
Two 3inch SiC boules were grown in a PVT setup using source material of different packing density. During the growth, in-situ computed tomography of the growing boules showed differences in the development of the growth interface. A slightly bent growth interface was found for the smaller packing density. For the higher packing density the resulting crystal exhibits the onset of 6 pyramidal facets on its flanks. Besides that, strong anisotropic lateral growth was found on its (000-1) facet. Numerical simulations show an impact of the powder on the thermal gradient in the growth cell and therefore on the supersaturation. It is discussed that a higher supersaturation can account for the anisotropy in the growth rate of the [1-100] and the [11-20] direction.<br
Keywords: Packing density; Supersaturation; Facet; In situ CT; Anisotropic lateral growth

Impact of Varying Parameters on the Temperature Gradients in 100 mm Silicon Carbide Bulk Growth in a Computer Simulation Validated by Experimental Results - Steiner, Johannes; Arzig, Matthias; Denisov, Alexey; Wellmann, Peter (Crystal Research and Technology, 2020)
The investigation of the interplay of experimental crystal growth runs and computer simulations of the physical vapor transport (PVT) growth process of silicon carbide (SiC) strongly supports the development of the growth technology toward larger crystalline diameters. To apply computer-aided designs of the growth process, a material database is developed that enables quantitative calculations of the temperature distribution inside the growth setup. The model utilizing COMSOL Multiphysics is validated by experimental means using five 100 mm SiC crystal growth runs, two measurement runs in a 100 mm PVT setup, and one SiC crystal growth run in a 75 mm PVT setup, varying in power, pressure, coil position, and reactor geometry. Material data are varied and the impact on the thermal gradients is investigated to trace out critical and noncritical parameters for the accuracy of the simulation. The influence of ambient pressure on the isolation's performance is studied experimentally and this correlation is implemented into the model. Beyond the state of the art, this work presents a modeling approach and handling of material properties for a true scale up of the current 100 mm and 150 mm SiC sublimation growth technologies to 200 mm.
CRIS-Team Scopus Importer:2019-08-27
Keywords: heat flux; induction heating; numerical simulation; physical vapor transport; silicon carbide

Influence of morphological changes in a source material on the growth interface of 4H-SiC single crystals - Arzig, Matthias; Steiner, Johannes; Salamon, Michael; Uhlmann, Norman; Wellmann, Peter (Materials, 2019)
In this study, the change of mass distribution in a source material is tracked using an in situ computer tomography (CT) setup during the bulk growth of 4H- silicon carbide (SiC) via physical vapor depostion (PVT). The changing properties of the source material due to recrystallization and densification are evaluated. Laser flash measurement showed that the thermal properties of different regions of the source material change significantly before and after the growth run. The Si-depleted area at the bottom of the crucible is thermally insulating, while the residual SiC source showed increased thermal conductivity compared to the initially charged powder. Ex situ CT measurements revealed a needle-like structure with elongated pores causing anisotropic behavior for the heat conductivity. Models to assess the thermal conductivity are applied in order to calculate the changes in the temperature field in the crucible and the changes in growth kinetics are discussed.
CRIS-Team Scopus Importer:2019-08-30
Keywords: Computer Tomography; Growth kinetics; In-situ CT; Laser flash; Numerical modelling; Source material; Supersaturation; Thermal conductivity

Influence of the growth conditions on the formation of macro-steps on the growth interface of SiC-Crystals - Arzig, Matthias; Künecke, Ulrike; Salamon, Michael; Uhlmann, Norman; Wellmann, Peter (Journal of Crystal Growth, 2021)
Several SiC crystals were grown in the same temperature field with a variation of the gas phase and the resulting step morphologies on the surface are analyzed using Laser Scanning Microscopy (LSM). It is shown that the step morphology changes due to doping, but also due to different C/Si ratios in the gas phase. By the addition of graphite into the source powder a reduction of Si-excess was achieved and an ordered step structure with an average height of 0.014 µm and width of 5.0 µm was formed. In the n-type doped case (n = 5.9∙1018 cm−3) the morphology on the facet differs strongly. Bunched steps with heights of 0.17 µm and widths of 152 µm are found. Between the diverse large macro-steps, a very ordered structure of unit cell height steps with a step spacing of 13.3 µm is found by Field Emission Scanning Electron Microscopy (FESEM) and Atomic Force Microscopy (AFM). A different change in the step morphology occurs over the whole crystal surface when elemental silicon is added into the source material. In contrast to the doping induced case, the bunched steps are more closely spaced and exhibit average heights of 0.20 µm and widths of 22 µm. The steps are noticeably retained at defects like micropipes or threading dislocations. The N2 induced step bunching is related to step kinetics on the main facet but the formation of macro-steps in the Si-rich case is assigned to the formation of stable surface steps. The variation of the inert gas pressure in the growth cell also changes the C/Si ratio in the gas phase as the diffusion from source to seed of the reactive gas species is affected differently. With a low inert gas pressure of 0.2 mbar a larger C/Si ratio in the gas phase is formed leading to steps with heights too small for analysis in the LSM, while the growth in 40 mbar promotes a smaller C/Si ratio leading to the formation of bunched steps with heights of 0.10–0.20 µm and with an average distance of 4.3 µm between them. The crystals grown in a gas phase comprising a large C/Si ratio show a better polytype stability than the crystals grown in Si-rich conditions. The instabilities can partly be attributed to the pile up of the macro-steps at defects exposing large 0001¯ terraces, where 2D-nucleation of foreign polytypes can occur.
CRIS-Team Scopus Importer:2021-10-29
Keywords: A1 Surface structure; A1. Optical microscopy; A1. Step bunching; A2. Growth from vapor; A2. Single crystal growth; B1 silicon carbide

Influence of the growth interface shape on the defect characteristics in the facet region of 4H-SiC single crystals - Arzig, Matthias; Salamon, Michael; Hsiao, Ta Ching; Uhlmann, Norman; Wellmann, Peter (Journal of Crystal Growth, 2020)
Two 75 mm 4H-SiC single crystals are grown by the physical vapor transport (PVT) technique, using different insulation materials. The insulation material of higher thermal conductivity led to an increased radial temperature gradient. The evolution of the growth front was monitored using the in-situ computed tomography (CT). A slightly bent growth interface and a bigger facet are formed during the growth applying a lower radial temperature gradient while a smaller facet and steeper crystal flanks are formed in the case of the larger radial temperature gradient. Micropipes are deflected laterally by large surface steps on the steep crystal flanks and a reduction of threading edge dislocations by 60% is revealed by KOH defect etching.
CRIS-Team Scopus Importer:2019-12-31
Keywords: A1. Crystal morphology; A1. Defects; A1. Surface structure; A2. Growth from vapor; A2. Single crystal growth; B2. Semiconducting silicon compounds

Investigation of the growth kinetics of SiC crystals during physical vapor transport growth by the application of in-situ 3D computed tomography visualization - Arzig, Matthias; Salamon, Michael; Uhlmann, Norman; Wellmann, Peter (Advanced Engineering Materials, 2019)
Computed tomography using X‐rays has been applied during bulk growth of SiC in order to investigate growth kinetics in‐situ during the physical vapor transport process. Besides the standard SiC source material, in particular a pure solid source SiC block is used. It is found that the growth rate is lowered as the sublimation of gaseous species is limited to the top part of the solid source. The morphological changes in the source area during growth differ significantly compared to the process when conventional powder is used. The formation of multiple growth centers on the surface of the seed is monitored in‐situ with a computed tomography system. In a series of experiments the influence of the supersaturation on the growth is examined. The in‐situ computed tomography shows that the curvature of the growth interface is stronger influenced by the thermal field at higher pressures. A high supersaturation leads to the formation of rather smooth surface morphologies while the formation of large steps on the surface was induced at lower supersaturation
Keywords: SiC; solid source; supersaturation; in-situ CT; facet

Investigation of the Nucleation Process During the Initial Stage of PVT Growth of 4H-SiC - Strüber, Sven; Arzig, Matthias; Steiner, Johannes; Salamon, Michael; Uhlmann, Norman; Wellmann, Peter (Solid State Phenomena, 2023)
Due to high growth temperatures during the physical vapor transport (PVT) it is still almost impossible to gain proper insight into the actual growth conditions. Therefore, computer tomography (CT) is used as an in-situ monitoring during the crystal growth process. With the help of this technique, it is possible to observe the nucleation centers during the initial stage of growth (CT after 0 h) of a 4H-SiC single crystal. These growth islands are likely formed before the actual growth conditions are reached. Raman investigations of the area around a growth island located directly on the interface between seed and grown crystal is used to support this assumption. In addition, optical analysis after KOH etching were made to reveal the defects around the growth island. The island exhibits a inhomogeneous doping concentration in comparison to the surrounding grown crystal.
CRIS-Team Scopus Importer:2023-06-23
Keywords: 4H-SiC; initial stage; nucleation; PVT; Raman; X-ray in-situ visualization (CT)

Low temperature formation of CuIn1 - xGaxSe2solar cell absorbers by all printed multiple species nanoparticulate Se + Cu-In + Cu-Ga precursors - Möckel, Stefan; Wernicke, Tobias; Arzig, Matthias; Köder, Philipp; Brandl, Marco; Ahmad, Rameez; Distaso, Monica; Peukert, Wolfgang; Hock, Rainer; Wellmann, Peter (Thin Solid Films, 2015)
In this work an all nanoparticulate precursor for application in Cu(InGa)Sesolar cell absorbers is presented. Binary Cu-In nanoparticles, Cu-Ga powder and elemental Se nanoparticles were mixed in dispersion and deposited on Mo-coated substrates. Research was focused on Cu(InGa)Selayer formation kinetics, phase composition characterised by differential scanning calorimetry and in-situ X-ray diffraction (XRD). Furthermore phase composition and morphology were studied by ex-situ XRD, Raman spectroscopy and scanning electron microscopy. The results revealed a fast consumption of the precursor and the formation of CuInSebelow 340 °C. Binary secondary phases were not observed at any temperature.
Keywords: Low-temperature; Copper indium gallium diselenide; Chalcopyrite; Nanoparticulate precursors; In-situ X-ray diffraction; Bimetallic nanoparticles

Optimization of the SiC Powder Source Material for Improved Process Conditions During PVT Growth of SiC Boules - Ellefsen, Oda Marie; Arzig, Matthias; Steiner, Johannes; Wellmann, Peter; Runde, Pål (Materials, 2019)
We have studied the influence of different SiC powder size distributions and the sublimation behavior during physical vapor transport growth of SiC in a 75 mm and 100 mm crystal processing configuration. The evolution of the source material as well as of the crystal growth interface was carried out using in situ 3D X-ray computed tomography (75 mm crystals) and in situ 2D X-ray visualization (100 mm crystals). Beside the SiC powder size distribution, the source materials differed in the maximum packaging density and thermal properties. In this latter case of the highest packaging density, the in situ X-ray studies revealed an improved growth interface stability that enabled a much longer crystal growth process. During process time, the sublimation-recrystallization behavior showed a much smoother morphology change and slower materials consumption, as well as a much more stable shape of the growth interface than in the cases of the less dense SiC source. By adapting the size distribution of the SiC source material we achieved to significantly enhance stable growth conditions.
CRIS-Team Scopus Importer:2019-10-29
Keywords: Crystal growth; In situ visualization; SiC; Source material; Sublimation

Optimization of the SiC powder source size distribution for the sublimation growth of long crystal boules - Arzig, Matthias; Hsiao, TaChing; Wellmann, Peter (Advanced Materials Proceedings, 2018)
In this work we studied the influence of three different SiC powder size distributions and the sublimation behavior during physical vapor transport growth of SiC in a 3 inch crystal processing configuration. The evolution of the source material as well as of the crystal growth interface was carried out using in‐site X‐ray computed tomography. Two SiC powders exhibited a single modal D90 size distribution of ca. 50 μm and ca. 200 μm, respectively. In both cases the average SiC powder density was 1.2 g/cm3. The third powder was a mixture of the above mentioned source materials and exhibited a bimodal particle size distribution. The corresponding average SiC powder density was 1.7 g/cm3. In this latter case the in‐itu X‐ray computed tomography study revealed an improved growth interface stability that enabled a much longer crystal growth process. During process time, the sublimation‐recrystallization behavior of the mixed SiC powder showed a much smoother morphology change and slower materials consumption as well as much more stable shape of the growth interface than in the case of the less dense SiC source. By adapting the size distribution of the SiC source material we achieved to significantly enhance stable growth conditions.<br
Keywords: Silicon carbide; physical vapor transport; source material; in-situ visualization; computed tomography

Optimization of the SiC powder source size distribution for the sublimation growth of long crystals boules - Steiner, Johannes; Arzig, Matthias; Hsiao, Ta Ching; Wellmann, Peter (Materials Science Forum, 2019)
The influence of four different SiC source powder size distributions on the sublimation behavior during physical vapor transport growth of SiC was studied. The growth processes were carried out in a 3 inch crystal growth setup and observed in situ using advanced 3D computed tomography X-ray visualization. The single modal D90 size distribution of two source powders was 50 µm and 200 µm, respectively, with a corresponding average powder density of 1.17 g/cm³. The third source powder consisted of a blend of the previously named powders and exhibited an average powder density of 1.66 g/cm³ with a bimodal particle size distribution. The last source was composed of a solid polycrystalline SiC cylinder. The bimodal powder source exhibited a smoother morphology change and material consumption during the growth run and led to a much more stable shape change of the growth interface compared to the single modal source powders. The solid source featured the least morphology change. Therefore, with a careful adaption of the source material stable growth conditions can be achieved.
CRIS-Team Scopus Importer:2019-09-17
Keywords: Computed tomography; In-situ visualization; Physical vapor transport; Silicon carbide; Source material

Review of Sublimation Growth of SiC Bulk Crystals - Wellmann, Peter; Arzig, Matthias; Ihle, Jonas; Kollmuß, Manuel; Steiner, Johannes; Mauceri, M.; Crippa, D.; Lavia, F.; Salamon; Uhlmann, N.; Roder, M.; Danilewsky, A.; et al. (Materials Science Forum, 2022)
The review on bulk growth of SiC includes a basic overview on the widely used physical vapor transport method for processing of 4H-SiC boules as well as the discussion of three current research topics: (a) Sublimation bulk growth of large area, freestanding cubic SiC, (b) in-situ Visualization of the PVT Process using 2D and 3D X-ray based imaging and (c) prediction of dislocation formation and motion in SiC using a continuum model of dislocation dynamics (CDD).
Created from Fastlane, Scopus look-up
Keywords: 3C-SiC; 4H-SiC; bulk growth; dislocations; X-ray in-situ visualization

The processing chain of the wide bandgap semiconductor SiC – How small steps enabled a mature technology - Wellmann, Peter; Steiner, Johannes; Strüber, Sven; Arzig, Matthias; Salamon, Michael; Uhlmann, Norman; Nguyen, Binh Duong; Sandfeld, Stefan (Diamond and Related Materials, 2023)
This work paper was presented as a keynote lecture at the international conference on diamond and related materials in Lisbon (Portugal) in the year 2022. This paper summarizes in the first part the processing chain of the semiconductor material SiC from the raw material to epitaxially-ready wafers as they are used for electronic device manufacturing. In the second part a current research study, the reduction of the basal plane dislocation density in SiC crystal growth is presented. Among other defects, basal plane dislocations belong to the more severe structural defects in SiC with respect to degradation during electronic device operation. In the third part the applicability of X-ray topography to reveal dislocations and other structural defects in SiC is outlined in a review style.
CRIS-Team Scopus Importer:2023-04-14
Keywords: Bulk crystal growth; Dislocations; Processing chain; Silicon carbide

Three-dimensional in-situ growth surveillance of bulky SiC crystals - Salamon, Michael; Arzig, Matthias; Wellmann, Peter; Uhlmann, Norman (Proceedings of the DIR 2019, 2019)
The integrated design of modern Computed Tomography systems, optimized to achieve the required environmental conditions for a scan, such as stable Temperature or low vibration has helped to widespread the CT method along non-destructive testing and coordinate measurement applications. For in-situ analysis of processes this integrated design is often limiting the application to processes with relatively low peripheral requirements and small footprint. In general, the in-situ process is adapted to the CT using an experimental environment. In cases a productive environment is required the CT has to adapt to the process and its environment. The complex structure of a physical vapor transport (PVT) reactor represents such a case. Inside an evacuated crucible heated inductively to approx. 2400 ° C, the deposition of silicon and carbon atoms takes place on a seed crystal. Over a period of about 100 to 200 hours, crystal of about 20 - 30 mm in height and currently 150 mm in diameter are grown. The growth kinetics depends strongly on the temperature field and further processes characteristics. The geometry of the interior of the crucible and the growth interface of the crystal are relevant parameters that can be observed during the process by means of computed tomography. The publication presents the integration of a CT system into a PVT crystal growing process with a crystal diameter of 75 mm and the challenges related to the absorption characteristics of the bulky crystal and the quality losses resulting from the applied region of interest scanning.<br
Keywords: Computed tomography; in situ analysis; crystal growth; SiC; physical vapour transport

Tracking of the growth interface during pvt-growth of SiC boules using a X-ray computed tomography setup - Arzig, Matthias; Salamon, Michael; Uhlmann, Norman; Wellmann, Peter (Materials Science Forum, 2019)
A crystal comprising various polytype switches was analyzed in detail. A very flat temperature profile together with an on axis seed are used to increase the probability for the nucleation of foreign polytypes during growth. Formation of foreign polytype occurred from thin lamella propagating from the edge of the main facet to the crystal rim as well as from 2D nucleation. The evolution of the crystal surface during the growth time is visualized using in-situ XRay computed tomography. Two concurrent growth centers are identified in the beginning of the growth process. Nucleation and lateral growth of foreign polytypes in the main facet area can be traced during the growth process.
CRIS-Team Scopus Importer:2019-09-17
Keywords: Computed tomography; In-situ visualization; Physical vapor transport; Polytype switch; Silicon carbide

X-Ray Computed Tomography specifically adapted for monitoring of dynamic processes in material science and chemistry - Salamon, Michael; Reisinger, S.; Schlechter, T.; Schmitt, M.; Hofmann, T.; Uhlmann, Norman; Schug, Sebastian; Arlt, Wolfgang; Fahlbusch, Lars; Arzig, Matthias; Wellmann, Peter (WCIPT8 - 8th WORLD CONGRESS ON INDUSTRIAL PROCESS TOMOGRAPHY, 2016)
X-ray computed tomography (CT) is an established method in non-destructive testing / evaluation (NDT / NDE) applications. A wide range of CT systems is available to the market distinct mainly by resolution properties. The process X-ray tomography application requires for an adaption of the process device which in some cases can be mounted on the rotation stage of the standard CT apparatus. Most representative examples are compact fatigue testing devices providing multiaxial forces to the tensile specimen encapsulated in a mostly X-ray transparent housing. This procedure is usually applied to relatively small and isolated samples. For processes that cannot be measured in an isolated environment, due to their size or other boundaries application specific CT systems can be developed using a large variety of X-ray components available on the market. In this contribution the Fraunhofer Development Centre for X-ray Technology (EZRT) shows application specific solutions realized in the past years for process monitoring in material science and chemistry. One focus of the contribution is the CT of packed distillation columns applied for the investigation of the fluid dynamics and transportation processes in different packing systems at the Institute of Separation Science and Technology, University of Erlangen-Nürnberg. Fluid dynamic parameters in distillation columns (like interfacial area, liquid hold-up and liquid film thickness on the packing or between two liquid phases) can be directly estimated from the recorded CT images of a packing cross section at different height positions along the column in operation. A segmentation process allows for a quantitative evaluation of the fluid behaviour corresponding to the packaging. The CT system is adapted to scan a chromatography or distillation column in its vertical orientation using a horizontally rotating X-ray gantry setup allowing for gravity affected measurements relevant in e.g. low pressure fluid systems. The setup allows for versatile applications with a CT scan rate of 1 Hz at a maximum resolution down to 70 microns for objects between 50 and 200 mm. This technique replaces today the commonly applied medical CT for such kind of experiments. Another presented example for a process adapted CT setup provides an insight into the Physical Vapor Transport (PVT) process at 2200°C allowing in-situ observation of the growth of SiC bulk crystals. The actual results achieved at the Crystal Growth Lab, University of Erlangen-Nürnberg by adaption of an X-ray tomography setup to a customized growth chamber setup will be presented and an outlook on the development tasks will be given.
Keywords: X-ray tomography; 4D-CT; Fluid dynamics; Crystal growth